Islamic fundamentalism : myths and realities - Moussalli, Ahmad S. ([S.l.] : Ithaca Press, 1998)
After the resurgence of Islamic activism in recent decades , Islamic fundamentalist groups today seem set to maintain their dominant position across a range of Middle and Near Eastern regimes. In this book, a range of leading Middle East academics come together to challenge and correct theoretical and pratical misconceptions about Islamic movements. The result is a volume which questions the process of abstraction - which leads to the creation of the myth of extremism - and offers an account of Islamic fundamentalist thought and movements that places them within their international, regional and local context. In Part I the contributors examine the theoretical, philosophical and political foundations of fundamentalist discourses and the construction of fundamentalist ideologies; in additon they investigate the tools used to study Islamic movements. Part II provides detailed case studies of developments in Algeria, Lebanon, the Occupied Territories, Saudi Arabia and Egypt. These in-depth chapters analyse the causes of the fundamentalist movements' successes and failures.